Atmospheric radiocarbon levels were highly variable during the last deglaciation - Talamo, Sahra; Friedrich, Michael; Adolphi, Florian; Kromer, Bernd; Heaton, Timothy J.; Cercatillo, Silvia; Muscheler, Raimund; Paleček, Dragana; Pelloni, Enrico; Tassoni, Laura; Toniello, Vladimiro; Wacker, Lukas (Communications earth & environment, 2023)
Radiocarbon dating provides a key chronological framework for studying past environmental changes. Raw radiocarbon ages measured in samples must be converted to calendar ages using an appropriate calibration curve. Tree-ring datasets provide the gold-standard for developing a precise curve of atmospheric radiocarbon levels over long-time scales. Here, we reconstruct atmospheric radiocarbon levels using a millennium-long section of tree-ring chronology segments that extend into the last glacial period. The samples were obtained from subfossil larch trees recovered from clay quarries at Revine, Italy. Our reconstruction shows higher variations in the amplitude of atmospheric radiocarbon between 18,475 and 17,350 calendar years before the present than that detected in the IntCal20 calibration curve. Comparing the new tree-ring based reconstruction with Beryllium-10 fluxes derived from ice cores, we hypothesise that these variations are driven by solar variability. Our results demonstrate the unique value of sub-decadal radiocarbon sequences derived from glacial tree-ring chronologies.
Gesehen am 06.08.2024